THE EFFECT OF THE HEALING MINERAL WATER "JO`YZAR" ON THE MUCOUS MEMBRANE OF THE STOMACH WALL - Shukhrat J. Teshaev; Nargiza A. Akramova (Central Asian Journal of Medicine, 2025)
The main function of the stomach is to digest food. Inside it are cells that produce digestive enzymes, called proteases, which convert complex food molecules into simple nutrients that can be assimilated by the cells of our organs and tissues. In addition, the stomach produces molecules called intrinsic factors. These proteins are important because when these nutrients pass through the intestines, they absorb vitamin B12, which is necessary for the production of red blood cells. Absorption of some nutrients also occurs in the stomach lining. Water, amino acids, caffeine, alcohol can pass through the stomach walls.